KEMAMPUAN REPRESENTASI MATEMATIS SISWA PADA MATERI BANGUN DATAR SEGIEMPAT DI SMP - Ardiansyah, Ardiansyah; Zubaidah, Zubaidah; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to determine the ability of students' mathematical representation on the building materials of the quadrangles in class VIII SMP Negeri 11 Sungai Raya. The research method used is descriptive research with survey research form. Subjects in this study were students of class VIII and determined by purposive sampling technique. The ability of a visual representation of symbolic representation forms, students create drawings, images have descriptions and meet some properties. The ability of a visual representation of verbal representation forms, students draw only a quadrangles the image has a description but does not meet every trait in the matter. The ability of symbolic representation of visual representations, students write symbols correctly, clearly, write character traits improperly and incompletely. The ability of symbolic representation of visual representation forms, students can write symbols correctly, clearly, and write characters with characters that are not correct and incomplete. The ability of verbal representation of the form of visual representation, the students write is incorrect, and incomplete, and the language used is less clear and precise. The ability of verbal representation of symbolic representation forms, students write improper, and incomplete, and the language used is less clear and precise. Keywords: Mathematical Representation,Â Studentâ€™s Mathematics Representation,Visual Representation, Verbal Representation, Symbolic representation